2000
DOI: 10.1111/1467-8624.00209
|View full text |Cite
|
Sign up to set email alerts
|

Mastery Motivation and Self‐Evaluative Affect in Toddlers: Longitudinal Relations with Maternal Behavior

Abstract: This study examined relations between maternal control and evaluative feedback during the second year of life and children's mastery motivation and expressions of self-evaluative affect a year later. Participants were 75 toddlers (35 girls, 40 boys) and their mothers. Maternal controlling behavior and evaluative feedback were examined while mothers taught their 24-month-olds a challenging task. Children's mastery motivation and expressions of self-evaluative affect were assessed during easy and difficult achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 35 publications
(53 reference statements)
5
119
1
5
Order By: Relevance
“…Around third year of their life, children display their annoyance if anyone exceeds standards. At 20 months, old, the children display unique feelings when their outcomes match, or fail to match standards (Kelly et al, 2000). Such feelings were expected to be a result of internalizing parental standards, through parental feedback.…”
Section: Effects Of Parental Relationships On the Formulation And Devmentioning
confidence: 99%
See 1 more Smart Citation
“…Around third year of their life, children display their annoyance if anyone exceeds standards. At 20 months, old, the children display unique feelings when their outcomes match, or fail to match standards (Kelly et al, 2000). Such feelings were expected to be a result of internalizing parental standards, through parental feedback.…”
Section: Effects Of Parental Relationships On the Formulation And Devmentioning
confidence: 99%
“…Lutkenhaus (1984) found out the same phenomenon; at 36 months old, the mother praise accompanied with satisfaction by smiles correlated positively with their children motivation during tasks, while, the physical interruption and criticizing notes were negatively correlated with child motivation. Also, it was proved that the high control of the mother decreases the pleasure of achieving the task, decreases persistence and sense of autonomy in young children, and correlated with low mastery motivation, avoiding challenge, and low interest in tasks that include achievement (Kelly et al, 2000).…”
Section: Effects Of Parental Relationships On the Formulation And Devmentioning
confidence: 99%
“…Heterogeneous groups of maltreated children, which have included neglected as well as physically and sexually abused children, exhibit elevated levels of shame [83,[89][90][91]. Similarly, children whose parents are negative and rejecting or who use an authoritarian style of parenting are at increased risk of exhibiting shame [83,89,[92][93][94].…”
Section: Family and Hereditary Factorsmentioning
confidence: 99%
“…Furthermore, Christenson, Hurley, Sheridan and Fenstermacher (1997) assert that variables related to parental attitudes and behaviour are more important than SES in predicting academic achievement. For example, Kelley, Brownell, and Campbell (2000) demonstrated that maternal positive feedback predicted the child's later persistence in tackling academic tasks, and maternal guidance resulted in less avoidance of challenging tasks a year later. Parental behaviour, and in turn academic success, appears to be linked to family structure.…”
Section: Developmental Perspectives Surrounding Risk and Resilience Imentioning
confidence: 99%